Journeys of Attachments, Trajectories of (Mis)fitting: Musicking in Deaf Communities in Montreal - Grenier, Line; Leduc, Véro (Troubling Inheritances: Memory, Music, and Aging, 2022)
This book provides an interdisciplinary focus on music, memory, and ageing by examining how they intersect outside of a formal therapeutic context or framework and by offering a counter-narrative to age as decline. It contributes to the development of qualitative research methodologies by utilizing and reflecting on methods for studying music, memory, and ageing across diverse and interconnected contexts. Using the notion of inheritance to trouble its core themes of music, memory, ageing, and methodology, it examines different ways in which the concept of inheritance is understood but also how it commonly refers to the practice of passing on, and the connections this establishes across time and space. It confronts the ageist discourses that associate popular music predominantly with youth and that focus narrowly, and almost exclusively, on music's therapeutic function for older adults. By presenting research which examines various intersections of music and ageing outside of a therapeutic context or framework, the book brings a much-needed intervention.